Toxicidade do herbicida Glifosato em Daphnia magna e pós-larvas de Rhamdia quelen - Bastos, Denise Nascimento de (2013)
The objective of this study was to avaluate the toxicity to Daphnia magna cultivated on a large scale and post-larvae of jundia (Rhamdia quelen) to Glyphosate herbicide and the reference substances. Were used daphnia with age between 2 and 26 hours of life, from large scale cultured arrays. There were performed six sensitivity assays that were composed of seven treatments and three replica, at concentrations of 0; 0.1; 0.3; 0.5; 0.7; 0.9 and 1.2 mg.L-1 of potassium dichromate, with 24 hours duration. The acute toxicity assays, with copper sulfate at concentrations of 0; 0.01; 0.025; 0.05; 0.075 and 0.10 mg.L-1, and to the glyphosate concentrations of 0; 11; 21; 31; 41 and 51 µg.L-1, with three and two replica respectively, and 48 hours duration. However the post-larvae of jundia were exposed to concentrations of 0; 0.5; 1.0; 1.5; 2.0 and 2.5 mg.L-1 of glyphosate, per 96 hours. Each replica was composed of a bottle with 10 individuals. The chronic toxicity test, the daphnia were exposed to concentrations of 0, 2, 4, 6, 8 and 10 µg.L-1 of glyphosate, with 10 replica, being a daphnia per replica, evaluating the survival and fecundity in 21 days. For acute toxicity assays, was calculated mortality using the Median Effective Concentration (EC50) in each test. The mean EC50 for D. magna with potassium dichromate was 0.57 mg.L-1. The value of acute toxicity for copper sulphate was reached at a concentration of 0.034 mg.L-1. And for the glyphosate the EC50 of 32 µg.L-1 is toxic for the species. The chronic assay showed high rate of mortality, possibly the result of unfavourable conditions for the large scale cultivation of arrays, hurt his endurance. For the R. quelen the EC50 was achieved at 0.9 mg. L-1. The results showed that organisms of the species D. magna cultivated on a large scale can be used in acute toxicity tests, but not in chronic toxicity testing, for the assessment of water quality.